2017
DOI: 10.1155/2017/9181729
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Similarities in Scale Models of a Single-Layer Spherical Lattice Shell Structure under the Effect of Internal Explosion

Abstract: The similarity of each scale model is verified based on the theory of similarity, deriving the similarity law of internal explosions in a single-layer spherical lattice shell structure via dimensional theory, calculated based on models with scaling coefficients of 1, 0.8, 0.6, 0.4, 0.2, and 0.1. The results show that the shock wave propagation characteristics, the distribution of the overpressure on the inner surface, the maximum dynamic response position, and the position at which the earliest explosion venti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Based on previous numerical simulation studies [5,7], it was generally believed that the initial pressure stage at the end cover pole was divided into two parts: first, the explosion shock wave inside the charge was encountered at the pole and the reflected pressure was generated. Then, the convergence collision wave of the shock wave was formed at the pole, and the convergence pressure was significantly higher than the first pressure peak.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous numerical simulation studies [5,7], it was generally believed that the initial pressure stage at the end cover pole was divided into two parts: first, the explosion shock wave inside the charge was encountered at the pole and the reflected pressure was generated. Then, the convergence collision wave of the shock wave was formed at the pole, and the convergence pressure was significantly higher than the first pressure peak.…”
Section: Resultsmentioning
confidence: 99%
“…V. Pickerd et al [6], through experiments and numerical simulation, found that the second peak was much higher than the first peak, which was on the gauges at the edge and corner of the cubic explosive vessel. W. B. Wang et al [7] used numerical models with different zoom ratios to analyze the pressure load distribution of a single-layer spherical lattice shell structure, in which the maximum pressure at the pole always appeared at the second peak. Z. R. Li et al [8] experimentally measured the pressure, which was loaded on the cover plate of a cylindrical vessel, with an aspect ratio of 2:1, indicating that the pressure load on it presented multiple wave peaks, and the maximum peak of the pressure load at the center of the cover plate was three times higher than the first.…”
Section: Introductionmentioning
confidence: 99%